Bronchogenic cancer: It still exists. (15th September 2015) - Strassen, Ulrich; Hofauer, Benedikt; Matsuba, Yumiko; Becker, Karen; Mansour, Naglaa; Knopf, Andreas
Abstract : Objectives/Hypothesis: Branchial cleft cysts rank among the most common differential diagnoses of cystic cervical masses. Rarely, classic cystic structures exhibit a squamous cell carcinoma differentiation that represents a bronchogenic carcinoma. The existence of bronchogenic carcinoma is controversial due to the lack of systematic immunohistologic workup. The present study aimed to identify the clinical and immunohistologic features of bronchogenic carcinoma to clearly distinguish this entity from other cystic cervical masses. Methods: Immunohistologic (epidermal growth factor receptor; cytokeratin 5, 6, 7, 13; and p16) and epidemiologic assessments were performed for branchial cleft cysts (n = 63), bronchogenic carcinomas (n = 5), cystic metastasized oropharyngeal carcinomas (n = 97), and carcinomas of unknown primary (n = 51). The study was conducted as a retrospective case series study with comparison. Results: The patients with bronchogenic carcinomas differed significantly in age and in the number of involved lymph nodes compared with the cystic metastasized oropharyngeal carcinoma (and carcinoma of unknown primary) patients. Regular histologic wall structures were only observed in the bronchogenic carcinomas and branchial cleft cysts. Solitary cytokeratin‐7 staining was only observed in the bronchogenic carcinomas, and all of the bronchogenic carcinomas were p16 negative. Conclusions: The existence of bronchogenic carcinoma seems to be plausible based on clinical findings. Cytokeratin‐7 and p16 staining might be helpful in the diagnostic workflow. Level of Evidence: 4 Laryngoscope, 126:638–642, 2016